2006
DOI: 10.1002/clc.4960290409
|View full text |Cite
|
Sign up to set email alerts
|

Depression and thyroid axis function in coronary artery disease: Impact of cardiac impairment and gender

Abstract: SummaryBackground: Increased rates of depression are reported in coronary artery disease (CAD). In heart disease, depression increases disability, reduces quality of life, and increases mortality.Hypothesis: The study was undertaken to examine the relationship between depression and thyroid axis function in patients with CAD.Methods: In all, 73 patients with CAD, consecutively admitted to a cardiac rehabilitation hospital, were assessed for depression using the Hospital Anxiety and Depression scale (HADS). Blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…In univariate analyses, lower T3 to T4 ratios were associated with greater depressive symptoms, suggesting that decreased activity of 5ʹ deiodinase can be related to depressive symptom severity in brain tumor patients. The association of low T3 concentrations with elevated depressive symptoms has been previously reported in medical patients, 13 and it was suggested that elevated hypothalamic-pituitary-adrenal axis activity in depressed patients can suppress 5ʹ deiodination leading to decreased T3 concentrations. 31 In addition, it is well established that depression is prevalent in hypothyroid patients.…”
mentioning
confidence: 69%
“…In univariate analyses, lower T3 to T4 ratios were associated with greater depressive symptoms, suggesting that decreased activity of 5ʹ deiodinase can be related to depressive symptom severity in brain tumor patients. The association of low T3 concentrations with elevated depressive symptoms has been previously reported in medical patients, 13 and it was suggested that elevated hypothalamic-pituitary-adrenal axis activity in depressed patients can suppress 5ʹ deiodination leading to decreased T3 concentrations. 31 In addition, it is well established that depression is prevalent in hypothyroid patients.…”
mentioning
confidence: 69%
“…In this study we used a validated Lithuanian translation of the HADS [Bunevicius and Zileniene, 1991], which is widely used in research studies [Bunevicius et al, 2006] in Lithuania. The HADS was administered as a paperand-pencil questionnaire that takes 2-5 min to complete.…”
Section: Methodsmentioning
confidence: 99%
“…The number and times of spontaneous deaths during the experimental period were carefully context and is considered a strong independent predictor of poor prognosis in cardiovascular disease evolution (19). In patients with coronary artery disease, lower T3 levels were related to greater NT-proBNP concentrations and with clinical features of heart failure (20,21). Furthermore, clinical studies have shown that levels of T3 have a positive correlation with ejection fraction (EF%) in ST-elevation myocardial infarction (STEMI) patients at 48 h from the index event (22).…”
Section: Experimental Protocolmentioning
confidence: 99%